Depression and its Association with Binge Eating Disorder and BMI - Rabia shehzad; Hafsa Amir; Farhana Ali; Zunaira Mehdi; Alishba Zafar; Nimra Nawaz; Qaiser Raza (International Health Review, 2024)
Depression is a grave mental disorder that often results in persistent feelings of loneliness, anger and sadness. It has been found that depression is linked to binge eating disorder (BED) and higher body mass index (BMI). The main objective of this cross-sectional study was to assess the presence of binge eating disorder, obesity and dietary patterns among depressed patients, and to examine the association of these factors with depression. The study included 87 depressed patients, both male and female, aged 20-40 years. The Patient Health Questionnaire-9 (PHQ-9), Binge Eating Disorder Screener-7, and Food Frequency Questionnaire were used to determine depression, BED & dietary intake, respectively. BMI was calculated to observe weight in relation to height. The data was collected from Fountain House and Security Social Hospital, Lahore. Out of the total 87 patients, 19 did not have BED, 16 had mild BED, and 52 had moderate to severe BED. Regarding BMI, 7 patients were underweight, 42 had a healthy weight, 27 were overweight and 11 were obese. The study revealed that a higher BMI had an association with depression, but no significant association was observed between BMI and BED. The study showed no association between BED and depression. Poor dietary patterns were also observed in depressed patients.